2017
DOI: 10.1016/j.ijdevneu.2017.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Pathobiological expression of the brain‐derived neurotrophic factor (BDNF) in cerebellar cortex of sudden fetal and infant death victims

Abstract: Brain-derived neurotrophic factor (BDNF), a neurotrophin of the central nervous system, is able to regulate neuronal differentiation and modulate synaptic plasticity, being particularly involved in the development of the cerebellar cortical structure. The main aim of this study was to delineate, by immunohistochemistry, the BDNF expression in human cerebellar cortex of victims of fetal and infant death. The study was performed on a total of 45 cases, aged between 25 gestational weeks and 6 postnatal months, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…We found that infants for whom, at the time of death, the parents had indicated a positive history of cigarette smoke exposure (be it the mother, father, both or any other household member), no change in BDNF expression was observed in the brainstem nuclei studied, yet an increase in proBDNF and decrease in TrkB was evident in the hypoglossal and vestibular nuclei, both having a role in respiratory control (Tang et al, 2011). A subsequent study from another laboratory showed that in the kolliker-fuse nucleus (also important for respiratory control), altered BDNF expression was evident amongst infants with cigarette smoke exposure (Lavezzi et al, 2014) and this was extended into the cerebellum showing decreased BDNF levels in both brain regions (Lavezzi et al, 2018). Combined, these studies provide the first reports that exposure of the developing human to pre-and/or postnatal cigarette smoke alters BDNF and TrkB expression in respiratory regulating regions and could have played a role in subsequent pathophysiology changes leading to death.…”
Section: Human Studies Of Nicotine On Bdnf and Trkbmentioning
confidence: 98%
“…We found that infants for whom, at the time of death, the parents had indicated a positive history of cigarette smoke exposure (be it the mother, father, both or any other household member), no change in BDNF expression was observed in the brainstem nuclei studied, yet an increase in proBDNF and decrease in TrkB was evident in the hypoglossal and vestibular nuclei, both having a role in respiratory control (Tang et al, 2011). A subsequent study from another laboratory showed that in the kolliker-fuse nucleus (also important for respiratory control), altered BDNF expression was evident amongst infants with cigarette smoke exposure (Lavezzi et al, 2014) and this was extended into the cerebellum showing decreased BDNF levels in both brain regions (Lavezzi et al, 2018). Combined, these studies provide the first reports that exposure of the developing human to pre-and/or postnatal cigarette smoke alters BDNF and TrkB expression in respiratory regulating regions and could have played a role in subsequent pathophysiology changes leading to death.…”
Section: Human Studies Of Nicotine On Bdnf and Trkbmentioning
confidence: 98%
“…These alterations comprised partial or total disruption of the argyrophilic nucleolar organizer region (AgNOR) of the Purkinje cells [28]. Related to the same syndromes, and similarly associated to maternal nicotine abuse, expression of the brain-derived neurotrophic factor (BDNF) was found to be significantly depressed in the granule layers of the cerebellar cortex, chiefly the posterior lobule, a region involved in respiratory control [29]. This implies degeneration in synaptic transmission in the respiratory circuits, with obvious deleterious consequences for survival.…”
Section: Toxic Action On Neuronal Structuresmentioning
confidence: 99%
“…The involvement of some NTs has also been hypothesized in post-mortem research involving infants affected by SIDS. Significant alterations in BDNF levels in the pontine KFN have been reported in a wide number of sudden intrauterine unexplained death syndrome (SIUDS) and SIDS cases [ 99 ]. In another study, low BDNF levels in different cerebral regions involved in respiratory control were found in children who died of SIDS.…”
Section: Nts In the Neonatal Periodmentioning
confidence: 99%